Work Effectiveness of Human Resources in The Management of Ship Extension and Issuance of Ship Documents at PT Sumberbumi Global Niaga - Bagus Dwi Prasetio; A.Chalid Pasyah; Muchlas Hamdani; Denny Fitrial (Greenation International Journal of Economics and Accounting, 2023)
Ship certificates and documents are important documents that must be pocketed by every company or individual who wants to operate his ship. Certificates and documents are a form of legal evidence owned by each ship to obtain permits and fishing eligibility under government laws and regulations. These letters are intended as a guarantee for the security and safety of humans, ships and various forms of cargo in them. As is known, there are so many types of accidents that occur in various waters caused by the negligence of the crew. They ignore the licensing and feasibility of fishing through certification that has been regulated in the regulations. This is what causes all forms of loss during the voyage to be very difficult to avoid. To get these important certificates and documents, of course, there are several requirements and conditions that must be met. After all the requirements are met, then all files for submitting a ship certificate will be processed. Before sailing, a ship must complete the completeness of the ship's documents first. This is done so that shipping activities become legal and avoid being ticketed. Not only to avoid ticketing, the completeness of documents can also make it easier for ships to enter the port area. Documents for the completeness of the ship are also evidence that the ship is fit for sailing and has completed the bureaucracy in accordance with the law. The approach method used is qualitative, while the data collection techniques use observation, documentation, and interviews.